Few durable layers suppress cotton combustion due to the joint combination of layer by layer assembly and UV-curing. Issue 87 (20th September 2015) - Carosio, Federico; Alongi, Jenny
<x xml:space="preserve">Abstract</x> In the last five years, Layer by Layer (LbL) assembly has proven to be one of the most innovative solutions for conferring flame retardancy to fabrics.